2008
DOI: 10.2478/v10035-008-0085-3
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Efficacy of a Local Vs Brachial Plexus Block Anaesthesia in the Carpal Tunnel Release: The Results of a Prospective and Randomised Trial

Abstract: Carpal tunnel release can be performed in local anaesthesia, peripheral nerves blocks (either proximally or distally), intravenous regional (Bier block) and general anaesthesia. To our knowledge, in Poland operations of carpal tunnel syndrome are routinely performed under brachial plexus block anaesthesia. The aim of the study was to compare the effectiveness of local versus brachial plexus block anaesthesia for carpal tunnel decompression. Material and methods. One hundred and fifty-five patients diagnosed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Recent developments in the surgical treatment of carpal tunnel syndrome have resulted in improved surgical techniques to reduce postoperative pain and improve cosmesis. In small incision surgery, the transverse carpal ligament can also be excised to fully decompress the carpal tunnel, which leads to improved efficacy, particularly in terms of functional improvement and reduced scar hyperplasia [1012]. Also, in small incision surgery, the requirements for surgical instruments and equipment are low, the surgical approach is simpler, tissue damage is smaller, and the medical costs are lower [13].…”
Section: Discussionmentioning
confidence: 99%
“…Recent developments in the surgical treatment of carpal tunnel syndrome have resulted in improved surgical techniques to reduce postoperative pain and improve cosmesis. In small incision surgery, the transverse carpal ligament can also be excised to fully decompress the carpal tunnel, which leads to improved efficacy, particularly in terms of functional improvement and reduced scar hyperplasia [1012]. Also, in small incision surgery, the requirements for surgical instruments and equipment are low, the surgical approach is simpler, tissue damage is smaller, and the medical costs are lower [13].…”
Section: Discussionmentioning
confidence: 99%
“…Direct comparisons between regional and local anesthesia conducted thus far have indicated a slight physician preference for local techniques because of their simplicity, lower cost, and patient preference due to motor function preservation. 69,70 Flexor tenosynovectomy (5 percent) and intraoperative steroid injection (2 percent) were reported in the tracer; however, their efficacy in augmenting carpal tunnel release is unknown (Table 3). [71][72][73][74] Studies performed thus far have indicated no significant differences in patient outcomes following the use of these adjunctive treatments.…”
Section: Future Research Directionsmentioning
confidence: 99%